Practicamos hábitos de higiene personal, cuidando la salud - Serna Jimenez, Monica Mary (2021)
The purpose of this work of professional sufficiency is to promote significant learning referred to the session entitled: "" We practice personal hygiene habits, taking care of health ", developed in the area of social personnel for the initial education level, taking into account the competence of: "Build your identity", achieving the performance of planning, of taking the initiative to carry out daily activities from their interests, performing personal care actions, adapting to the saying and textual type according to the communicative purpose, and incorporating a relevant vocabulary as well as some terms typical of the fields of knowledge. The practice of good habits is intended to create awareness in the student and that these habits are permanent in his life. The learning session was evaluated through direct observation and guidance and corrections were given to each of the students who needed it.